2010
DOI: 10.1111/j.1574-6968.2010.01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of swarming motility in Rhizobium leguminosarum bv. viciae

Abstract: We have characterized swarming motility in Rhizobium leguminosarum strains 3841 and VF39SM. Swarming was dependent on growth on energy-rich media, and both agar concentration and incubation temperature were critical parameters for surface migration. A cell density-dependent lag period was observed before swarming motility was initiated. Surface migration began 3-5 days after inoculation and a full swarming phenotype was observed 3 weeks after inoculation. The swarming front was preceded by a clear extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
(69 reference statements)
0
31
0
Order By: Relevance
“…The roles of these regulators in the expression of flagellar and chemotaxis genes in R. leguminosarum were determined by cloning the orthologous genes from the sequenced strain 3841 and our laboratory strain VF39SM. We used both strains because these strains exhibit differences in the pattern of flagellation (Tambalo et al, 2010) and also in swarming motility (Tambalo et al, 2010). Strain VF39SM is peritrichously flagellated, while 3841 has one to two subpolar flagella.…”
Section: Tambalo and Others Unpublished Results)mentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of these regulators in the expression of flagellar and chemotaxis genes in R. leguminosarum were determined by cloning the orthologous genes from the sequenced strain 3841 and our laboratory strain VF39SM. We used both strains because these strains exhibit differences in the pattern of flagellation (Tambalo et al, 2010) and also in swarming motility (Tambalo et al, 2010). Strain VF39SM is peritrichously flagellated, while 3841 has one to two subpolar flagella.…”
Section: Tambalo and Others Unpublished Results)mentioning
confidence: 99%
“…We performed the studies using strains 3841 and VF39SM because the two strains exhibit substantial differences in pattern of flagellation and swarming motility (Tambalo et al, 2010). Using transcriptional fusions to a large number of genes involved in chemotaxis and motility, we demonstrate that only a subset of these genes is regulated by the VisN/R cascade.…”
Section: Introductionmentioning
confidence: 99%
“…viciae VF39SM (Priefer 1989) and a R. leguminosarum VF39SM strain containing a flagellin A (flaA)-gusA transcriptional fusion (Tambalo et al 2010b). The strains were routinely grown in TY (tryptoneyeast extract) broth (Beringer 1974) or swarm medium (Tambalo et al 2010c) using the following antibiotic concentrations: streptomycin, 500 g·mL −1 ; and tetracycline, 5 g·mL −1 . The basal swarm medium contained the following: 0.01% K 2 HPO 4 , 0.01% NaCl, 0.02% MgSO 4 ·7H 2 O, 0.04% KH 2 PO 4 , 0.4% yeast extract, 0.2% glycerol, and 0.7% Difco Bacto agar.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Swarming in R. leguminosarum (Tambalo et al 2010c) and the closely related species Rhizobium etli (Daniels et al 2006) have recently been reported and partially characterized. In R. leguminosarum bv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation